Aquatic Life Water Quality Criteria for Selected Pesticides - Tjeerdema, Ronald S.; Tjeerdema, Ronald S. (Reviews of Environmental Contamination and Toxicology, Continuation of Residue Reviews,, 2012)
Special Foreword Foreword Preface Aquatic Life Water Quality Criteria Derived via the UC Davis Method I. Organophosphate Insecticides Amanda J. Palumbo, Patti L. TenBrook, Tessa L. Fojut, Isabel R. Faria and Ronald S. Tjeerdema Aquatic Life Water Quality Criteria Derived via the UC Davis Method II. Pyrethroid Insecticides Tessa L. Fojut, Amanda J. Palumbo & Ronald S. Tjeerdema Aquatic Life Water Quality Criteria Derived via the UC Davis Method III. Diuron Tessa L. Fojut, Amanda J. Palumbo & Ronald S. Tjeerdema Index.